Effects of stair riser height on ankle proprioception in individuals with and without chronic ankle stability - Wang, Xueying; Wang, Zheng; Adams, Roger; Gao, Yang; Lyu, Jie; Han, Jia (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundAnkle sprains during stair descent are prevalent, especially in those with chronic ankle instability (CAI), which may be attributed to diminished ankle proprioception associated with CAI.ObjectiveThis study aimed to determine whether individuals with CAI have lower ankle proprioceptive performance during stair descent and to determine to what extent stair riser height may affect ankle proprioception.Methods40 university students, including 21 CAI (9 males and 12 males, mean age 22.38 years, mean height 169.97 cm and mean weight 64.88 kg) and 19 healthy controls (11 males and 8 males, mean age 23.05 years, mean height 169.42 cm and mean weight 65.18 kg) volunteered. The Ankle Inversion Discrimination Apparatus for Stair Descent (AIDASD) was used to measure ankle inversion proprioception across 3 different riser heights: 15 cm, 17.5 cm, and 20 cm during stair descent.ResultsANOVA showed that individuals with CAI performed significantly worse than health group across all tested riser heights (F = 44.066, p < 0.001), with a significant main effect of riser height (F = 13.288, p < 0.001). Significant differences in proprioceptive acuity were found between 15 cm and higher risers (p < 0.001), but not between 17.5 cm and 20 cm (p = 0.675), alongside a significant linear downward trend with increasing riser height (F = 15.476, p < 0.001). No significant interaction was observed between the group and riser height (F = 0.745, p = 0.478).ConclusionThe presence of ankle instability and increased riser height significantly negatively affected ankle inversion proprioceptive performance during stair descent, which may increase the risk of ankle sprain.ApplicationPotential applications of this research include the assessment of ankle proprioception during stair descent attributable to effective ankle instability rehabilitation and riser height selection for safe stair design.